Crustal‐scale fluid flow during the tectonic evolution of the Bighorn Basin (Wyoming, USA). (19th August 2013) - Beaudoin, Nicolas; Bellahsen, Nicolas; Lacombe, Olivier; Emmanuel, Laurent; Pironon, Jacques
Abstract Stable isotope measurements (O, C, Sr), microthermometry and salinity measurements of fluid inclusions from different fracture populations in several anticlines of the Sevier‐Laramide Bighorn basin (Wyoming, USA) were used to unravel the palaeohydrological evolution. New data on the microstructural setting were used to complement previous studies and refine the fracture sequence at basin scale. The latter provides the framework and timing of fluid migration events across the basin during the Sevier and Laramide orogenic phases. Since the Sevier tectonic loading of the foreland basin until its later involvement into the Laramide thick‐skinned orogeny, three main fracture sets (out of seven) were found to have efficiently enhanced the hydraulic permeability of the sedimentary cover rocks. These pulses of fluid are attested by calcite crystals precipitated in veins from hydrothermal (T > 120 °C) radiogenic fluids derived from Cretaceous meteoric fluids that interacted with the Precambrian basement rocks. Between these events, vein calcite precipitated from formational fluids at chemical and thermal equilibrium with surrounding environment. At basin scale, the earliest hydrothermal pulse is documented in the western part of the basin during forebulge flexuring and the second one is documented in basement‐cored folds during folding. In addition to this East/West diachronic opening of the cover rocks to hydrothermal pulses probably controlled by the tectonic style, a decrease in 87/86Sr values from West to East suggests a crustal‐scale partially squeegee‐type eastward fluid migration in both basement and cover rocks since the early phase of the Sevier contraction. The interpretation of palaeofluid system at basin scale also implies that joints developed under an extensional stress regime are better vertical drains than joints developed under strike‐slip regime and enabled migration of basement‐derived hydrothermal fluids.